2014
DOI: 10.1515/bmt-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

New concepts and materials for the manufacturing of MR-compatible guide wires

Abstract: This paper shows the development of a new magnetic resonance imaging (MRI)-compatible guide wire made from fiber-reinforced plastics. The basic material of the developed guide wire is manufactured using a specially developed micro-pullwinding technology, which allows the adjustment of tensile, bending, and torsional stiffness independent from each other. Additionally, the micro-pullwinding technology provides the possibility to vary the stiffness along the length of the guide wire in a continuous process. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Until now, metallic guidewires, an important adjunct for X-ray fluoroscopy catheterization, have not been used during CMR fluoroscopy catheterization out of concern that long conductive structures will heat by coupling electrically with radiofrequency (RF) excitation pulses [ 7 , 8 ]. Glass and other non-metallic guidewires have been reported for CMR catheterization but suffer insurmountable fragility that will likely preclude wide adoption [ 9 12 ]. Non-conductive metallic guidewires have been reported that resist heating during CMR but that are not yet commercially available [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, metallic guidewires, an important adjunct for X-ray fluoroscopy catheterization, have not been used during CMR fluoroscopy catheterization out of concern that long conductive structures will heat by coupling electrically with radiofrequency (RF) excitation pulses [ 7 , 8 ]. Glass and other non-metallic guidewires have been reported for CMR catheterization but suffer insurmountable fragility that will likely preclude wide adoption [ 9 12 ]. Non-conductive metallic guidewires have been reported that resist heating during CMR but that are not yet commercially available [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consolidated fibre/resin is then passed through a cooling device to ensure a dimensionally stable end product [130]. In attempt to manufacture guidewires with different mechanical properties along its length, the Fraunhofer IPT team developed the micro-pullwinding process [129], a process combining both pultrusion and filament winding. In this process, the pultruded profile (using glass fibres) is wrapped and consolidated with additional layers of high-strength synthetic fibres (e.g.…”
Section: Guidewires and Selective Cathetersmentioning
confidence: 99%
“…In this process, the pultruded profile (using glass fibres) is wrapped and consolidated with additional layers of high-strength synthetic fibres (e.g. Kevlar®) in several winding units to significantly enhance its torsional and radial stiffness (figures 11(f)-(i)) [129]. Moreover, since glass fibres are susceptible to buckling, the The core is grounded at its distal end to create a flexible distal end.…”
Section: Guidewires and Selective Cathetersmentioning
confidence: 99%
See 1 more Smart Citation
“…Up until now, catheters and guide wires have only been suitable for use under fluoroscopy. The project "MiGi" aims to close this gap [1]. The development of a novel guide wire should facilitate the application of alternative imaging techniques (MRI and ultrasound) during medical interventions.…”
mentioning
confidence: 99%